Proceedings of the ACM SIGPLAN 1994 Conference on Programming Language Design and Implementation 1994
DOI: 10.1145/178243.178251
|View full text |Cite
|
Sign up to set email alerts
|

Accurate static estimators for program optimization

Abstract: Determining the relative execution frequency of program regions is essential for many important optimization techniques, including register allocation, function inlining, and instruction scheduling. Estechniques, we identify 76% of the most frequently executed call sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Graham et al have noted that an execution profiler must attribute execution time in a way that is significant for the logical structure of a program as well as for its textual decomposition [7]. Wagner et al have used quantitative metrics to compare estimates from static analysis to those derived from profiles, and found that simple techniques for predicting branches and loop counts suffice to estimate intraprocedural frequency patterns with high accuracy [16]. A Markov model can also be combined with functionlevel information to produce the interprocedural frequency information.…”
Section: Related Workmentioning
confidence: 99%
“…Graham et al have noted that an execution profiler must attribute execution time in a way that is significant for the logical structure of a program as well as for its textual decomposition [7]. Wagner et al have used quantitative metrics to compare estimates from static analysis to those derived from profiles, and found that simple techniques for predicting branches and loop counts suffice to estimate intraprocedural frequency patterns with high accuracy [16]. A Markov model can also be combined with functionlevel information to produce the interprocedural frequency information.…”
Section: Related Workmentioning
confidence: 99%
“…A Markov process [38] is adopted to estimate the execution frequency of each basic block. Our analysis algorithm is executed based on these statically estimated execution frequencies.…”
Section: Probabilistic Alias Analysis Based On Static-assigned Probabmentioning
confidence: 99%
“…We sort basic blocks in the order of their execution frequency. For each basic block B, this can be estimated from both the loop nesting level of B and the execution frequency of B within its acyclic region based on the probability of each conditional branch [Wagner et al 1994]. Additionally, we use the profile information collected for conditional branches by our combined interpreter and dynamic compiler [Suganuma et al 2001] in order to enhance the accuracy of branch probabilities.…”
Section: Order Determination For Eliminationmentioning
confidence: 99%